Focused Groups Discussion (FGD) on the Role of Muslim-Based Organization (MBO) in Contemporary Indonesia - Jahar, Asep Saepudin (Studia Islamika, 2010)
The general aim of this FGD is to analyze the roles of MBOs in Indonesia and the participation of MBOs in the socio-political development of the society. To obtain in-depth qualitative data, the FGD is focused on the two largest MBOs in Indonesia: NU and Muhammadiyah. This is because to the present, the two MBOs represent two mainstreams of Indonesian Islam: modernist and tradisionalist. The FGD also looked at other MBOs which develop in certain cities, such as Perti in Padang and NW in Mataram. These two MBOs are, in fact, traditionally close to NU.DOI: 10.15408/sdi.v17i3.459